2020
DOI: 10.3390/v12080834
|View full text |Cite
|
Sign up to set email alerts
|

Differential Behaviours and Preferential Bindings of Influenza Nucleoproteins on Importins-α

Abstract: Influenza viruses are negative single-stranded RNA viruses with nuclear transcription and replication. They enter the nucleus by using the cellular importin-α/-β nuclear import machinery. Influenza nucleoproteins from influenza A, B, C and D viruses possess a nuclear localization signal (NLS) localized on an intrinsically disordered extremity (NPTAIL). In this paper, using size exclusion chromatography (SEC), SEC-multi-angle laser light scattering (SEC-MALLS) analysis, surface plasmon resonance (SPR) and fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…Once the gene segments reach the nucleus, the virus usurps host factors to cross the nuclear envelope. The host factor importin-α binds three overlapping NLS on the N-terminal tail of B-NP to facilitate nuclear transport [ 51 , 52 ]. Importin-α has been previously described as a species-determinant for IAV [ 12 , 53 ].…”
Section: Nuclear Replication Adaptationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the gene segments reach the nucleus, the virus usurps host factors to cross the nuclear envelope. The host factor importin-α binds three overlapping NLS on the N-terminal tail of B-NP to facilitate nuclear transport [ 51 , 52 ]. Importin-α has been previously described as a species-determinant for IAV [ 12 , 53 ].…”
Section: Nuclear Replication Adaptationsmentioning
confidence: 99%
“…To determine if a host restriction phenomenon has been observed during IBV genome replication, we considered host nuclear factors. The importin-α protein family has been identified as a critical factor for transporting the vRNPs from the cytoplasm into the nucleus [ 51 , 52 ]. However, current literature only highlights the interaction between IBV vRNPs and human importin-α.…”
Section: Summary and Future Research Directionsmentioning
confidence: 99%
“…Therefore, the non-classical NLS of an NP is essential for IAV replication [173]. Donchet et al reported the binding affinity of an NP to different α-importins; an NP had the highest affinity for importin-α7 and the lowest affinity for importin-α1 [174].…”
Section: Influenza a Virus (Iav)mentioning
confidence: 99%
“…Viral nucleoproteins from influenza A, B, C and D viruses possess a nuclear localization signal (NLS) localized on an intrinsically disordered extremity of nucleoproteins (NP TAIL ). In their work, Crepin and collaborators provided the first comparative study to dissect the interactions between the four NP TAILs and the four importins-α identified and provided important highlights of these complex translocation mechanisms [9].…”
mentioning
confidence: 99%